PEMBUATAN VIDEO PROMOSI PELATIHAN DI BALAI LATIHAN KERJA SAMBAS MENGGUNAKAN METODE MDLC - Uray Raka Amigraf Miletias; Noferianto Sitompul; Vanie Wijaya (P3M STMIK Profesional Makassar, 2023)
The workforce is highly needed in the country's economic development, where qualified labor can drive more productive development. The Training Center Unit of Sambas District Work Training Center is a facility that accommodates training activities which function to provide, enhance, and develop skills, productivity, discipline, work attitude, and work ethic. To attract public attention to participate in the training, an introduction to each training available at the Sambas District Work Training Center through visual media is required, in the form of promotional videos. This promotional video creation utilizes the MDLC method, which is a combination of visual media, sound, video, animation, and others. The MDLC method consists of six stages: Concept, Design, Material Collection, Production, Testing, and Distribution. The result of this research is the completion of a 5-minute promotional video in H264 1080p format, namely Mp4.